Treatment for Flexible Flatfoot in Children With Subtalar Arthroereisis and Soft Tissue Procedures - Li, Bing; He, Wenbao; Yu, Guangrong; Zhou, Haichao; Xia, Jiang; Zhao, Youguang; Zhu, Hui; Yu, Tao; Yang, Yunfeng (Frontiers in Pediatrics, 2021)
Background Children with flexible flatfoot is common in clinics and there is no unified conclusion on surgical treatment. And for some patients with severe deformities, the correction of the subtalar joint arthroereisis combine the release of the Achilles tendon or gastrocnemius muscle release is still not satisfactory. The main aim of the present study was to investigate the therapeutic outcomes of subtalar arthroereisis combined with Achilles tendon or gastrocnemius recession and medial soft tissue (spring ligament, talonavicular joint capsule, tibionavicular ligaments and tibiospring ligaments) tightening for treating flexible flatfoot with severe deformities. Methods 30 patients (32 feet) with pediatric flexible flatfoot who underwent subtalar arthroereisis and soft tissue procedures during January 2016 to January 2018. There were 18 males (20 feet) and 12 females (12 feet) with an average age of 9.5 years (range, 8-12 years). We used the AOFAS scores and VAS scores combined with angles measure to evaluate the preoperative and postoperative status. Results 30 patients (32 feet) were followed up for 25.3 months on average (range, 18-36 months). There was no infection. Postoperative foot pain, arch collapse, and other symptoms improved. At last follow-up, the Meary angle was decreased from 17.5°±4.4° to 4.1°±1.2° (P＜0.05), the talar-first metatarsal(AP) was decreased from 15.3°±3.1° to 4.8 °±1.3°(P＜0.05), The mean AOFAS score was rose from 66.6±5.8 to 88.6±7.9 (P＜0.05), the mean VAS score was decreased from 6.6±0.6 to 1.7±0.3(P＜0.05). Conclusion The subtalar arthroereisis combined with soft tissue procedures can effectively correct flexible flatfoot in children and it is a significant method for severe forefoot abduction reconstruction.